If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 20x + 42 = 2x + 14 Reorder the terms: 42 + 20x = 2x + 14 Reorder the terms: 42 + 20x = 14 + 2x Solving 42 + 20x = 14 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 42 + 20x + -2x = 14 + 2x + -2x Combine like terms: 20x + -2x = 18x 42 + 18x = 14 + 2x + -2x Combine like terms: 2x + -2x = 0 42 + 18x = 14 + 0 42 + 18x = 14 Add '-42' to each side of the equation. 42 + -42 + 18x = 14 + -42 Combine like terms: 42 + -42 = 0 0 + 18x = 14 + -42 18x = 14 + -42 Combine like terms: 14 + -42 = -28 18x = -28 Divide each side by '18'. x = -1.555555556 Simplifying x = -1.555555556
| 3+4(b-2)=-3b-33 | | 2x+2y=80 | | 3[2-(3j-6)]4[6j-(1-2j)]=4-5j | | 7.3=13.8-5b | | -57=-6(1+8n)-3n | | 12(5+2y)=4y-(6y-9y) | | 7.3=13.8 | | |x+9|=2x-6 | | 2(-1-7x)=114 | | 16x-65=4x+151 | | -9x^2-6x+15=0 | | 8z+8z=-9z-9-5z | | 8x+8x=-9z-9-5z | | 1+4x-6x=15 | | 10x^2-25-6=0 | | 16(x-3)=-80 | | -151-5x=73+2x | | 14(x+5)=98 | | |x-3|=8 | | 6x-6=2x+30 | | -6x^2-7x-2=0 | | -(x-1)+10=-3(x-3) | | x+4x=30.000 | | 11(x+3)=132 | | 7+9=-2(5x-8) | | 14=x-5x+10 | | 1.4(3x-68)=5x | | -8x-41=-5x+46 | | -8(x-5)-6=34 | | 3(2y+4)=2(2y-4) | | 7(x+4)=63 | | (3x-68)=5x |